Situation with protection of forests against illegal loggings in Russian Federation - Y.N. Gagarin; A.A. Dobrovolsky; A.P. Smirnov (Вопросы лесной науки, 2019)
Currently, the focus of international attention to forest issues has shifted from monitoring compliance with the principles of sustainable forest management to monitoring the legality of forest use, to the introduction of an international “regime of legality” in the forest sector. Opposition to illegal logging is growing in the world. The Russian Federation has a long and successful experience in preserving its forests, and has repeatedly initiated international agreements and negotiation processes on forest conservation, including the issue of illegal logging. Unfortunately, for a number of reasons, in the last five years, there have been no international activities and coordination activities of the Russian Federation in these processes. The forest legislation of the Russian Federation has no clear definition of “illegal logging”. Currently, illegal logging is detected mainly outside the boundaries of forest land – during the arrest of violators during transportation and / or sale of illegally harvested wood. This system is random (periodic raids, law enforcement operations) and allows to detect only a small part of offenses related to illegal logging. The volumes of illegal logging presented by official statistics do not correspond to real figures, they are underestimated many times. In this regard, the decisions taken by the state are either erroneous or do not reflect the depth of the existing problem. The current number of forest guards and their technical equipment do not allow for the adequate protection of forests, timely detection of illegal logging and bringing violators to justice. Decisions to replace forest protection with remote monitoring tools and information systems proved to be untenable. It is necessary to encourage state forest management bodies to receive maximum forest income in order to maintain a full-fledged, technically equipped forest protection. It is also necessary create a special fund of the Russian Federation for the forests protection and regeneration using cash inflow from the payments for the use of forests (by analogy with the creation of a system of road funds in the Russian Federation).